Optimizing Students’ Mastery of Sentence Construction Through Jumbled Words Activities: A Study of Grade XI at MAN 2 Parepare - Nurul Waliyya Alam; Munawir; Magdahalena Tjalla; Nur Asiza (English Language Education Department, Universitas Majalengka, 2026)
Grammatical knowledge plays an important role in English as a Foreign Language (EFL) learning; however, many students still experience difficulties in constructing grammatically correct sentences. This study aimed to investigate students’ sentence construction ability before and after the implementation of jumbled word activities and to determine whether there was a significant difference after the treatment. This study employed a quantitative approach with a pre-experimental one-group pretest-posttest design. The research was conducted at MAN 2 Parepare involving 30 students of class XI A1 selected through purposive sampling. The data were collected through pre-test and post-test sentence construction tasks and analyzed using descriptive and inferential statistics. The findings showed that the students’ mean score increased from 56.43 to 76.30. The paired sample t-test also revealed a significance value of p < 0.001, indicating a significant difference between the pre-test and post-test scores. Therefore, jumbled word activities were effective in improving students’ sentence construction mastery, particularly in constructing simple and compound sentences.